Erratum - Editor, (Archives of Rheumatology, 2010)
Re: "Measurement of Foot Bone Mineral Density in Rheumatoid Arthritis: Its Application and Clinical Relevance" (Turkish J Rheumatology 2010; 25: 56-62) Please be informed the Results section of the above article was published with inaccuracies. The corrected "Results" section is provided below. We regret any inconvenience. Results: The short-term precision for fBMD measurements by DEXA (14 healthy volunteers, 3 repeated measurements) was adequate with a coefficient of variation 2.18%. Bilateral foot BMD and axial (spinal and hip) BMD were significantly lower in patients compared to the controls. Right fBMD was significantly correlated with axial BMD. But fBMD did not correlate with disease duration and activity indices (RAI and FFI). A negative correlation was found between the total BMD of foot, Sharp-joint narrowing score (SJNS) and erosion score (SES). A negative relation was found between foot BMD and SJNS, SES and Larsen score of the hands.